Fyn is Induced by Ras/PI3K/Akt Signaling and is Required for Enhanced Invasion/Migration - Yadav, Vipin (2010)
Src family kinases (SFKs) are frequently over-expressed and/or activated in human cancers, and play key roles in cancer cell invasion, metastasis, proliferation, survival and angiogenesis. Allosteric activation of SFKs occurs through well-defined post-translational mechanisms, however the SFK member Fyn is over-expressed in multiple human cancers (prostate, melanoma, pancreatic, glioma, chronic myelogenous leukemia) and the mechanism of increased Fyn expression is unclear. Since activation of Ras oncogenes is a common oncogenic event leading to the activation of multiple effector pathways, we explored if Ras could induce Fyn expression. Retroviral transduction of the human keratinocyte cell line HaCaT with oncogenic H-Ras dramatically up-regulated Fyn mRNA (>100-fold, p<0.001), protein, and kinase activity without affecting Src levels or activity. Activation of Akt, but not MAPK or EGFR, was necessary and sufficient for induction of Fyn by H-Ras. Expression of active Fyn was sufficient to increase HaCaT cell migration and invasion, and the enhanced migration and invasion induced by H-Ras could be significantly blocked (70% reduction, p<0.01) by knockdown of Fyn with a specific siRNA or inhibition of SFKs with PP2. In addition, expression of Fyn in MDA-MB-231 breast cancer cells was dependent on PI3K activity and was involved in their invasive phenotype. Thus, the Ras/PI3K/Akt pathway can account for Fyn over-expression in cancers, and Fyn is a critical mediator of the Ras-stimulated invasive cell phenotype. These results support the development of therapeutic strategies targeting Akt/Fyn pathway to block migration and invasion of tumor cells.